Geology and composition of heavy metal from tar balls and surface sediments along Pantai Chendering, Marang, Terengganu. - Zureen Hasneeda Zainal Abidin (2017)
The geochemical study of surface sediments of Chendering area is located at Chendering beach coastal plain area, 103° 11’ 09” E, 5° 16’ 09” N. The objectives of this research are to produce the geological map, to investigate the concentration of heavy metal either solely from tar balls or anthropogenic sources, and to compare the values of the samples with background concentration values of heavy metal. Geological studies is carried out approximately of 25km² and based from field study, the metasedimentary rock of Sungai Perlis Bed that consist of meta-sandstone, meta-siltstone, sandstone, meta-shale and phyllite is found. Basically for geochemical studies 12 samples of surface sediments were collected for the analysis of 6 heavy metal elements which are Zn, Mn, Pb, Ni, Cr, and Cu. The solution is analyzed with Inductive Couple Plasma- Optimal Emission Spectroscopy (ICP-OES). The average concentrations of heavy metal of surface sediments display the following ascending pattern Cu < Pb < Ni < Cr < Zn < Mn with the value of range 0.100 < 0.331 < 0.633 < 0.905 < 3.226 ppm respectively. The comparison of sample concentrations value with background values shows that the concentration ranges of the study area far below the limitation value thus safe for human safety and environmental problems.